Development of Diagnostic, Formative and Summative Assessment Instruments in the PjBL Model to Stimulate Students' Critical and Creative Thinking Skills - Asiah, Sintya; Festiyed (Jurnal Penelitian Pendidikan IPA, 2024)
It is hoped that current education can produce human resources who have strong critical and creative thinking abilities. Students must have critical and creative thinking skills to be able to solve problems efficiently and effectively. The benchmark for determining student success in learning is through evaluation which includes measurements and assessments. The aim of this research is to develop diagnostic, formative and summative assessment instruments in the PjBL model to stimulate critical and creative thinking skills. This type of research is research & development using the ADDIE model. The results of this research obtained the validity of the assessment instrument in the project based learning model with a valid category. The level of practicality of the assessment instrument was categorized as practical by teachers and students. The results of the effectiveness of the knowledge aspect with the results of the pretest and posttest are seen from the classical completeness of each skill which has reached a level of completeness above the minimum expected score. The N-Gain value shows results that meet the high criteria.